1990
DOI: 10.1111/j.1600-051x.1990.tb01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies and loss of periodontal bone in patients with rheumatoid arthritis

Abstract: The number of teeth, % of alveolar bone loss, serum IgG, and serum antibodies to Bacteroides gingivalis, Capnocytophaga ochracea and Eubacterium saburreum were recorded in 37 patients diagnosed with rheumatoid arthritis (RA) and in an age- and sex-matched control group of 37 individuals free from RA. The RA group had a significantly increased loss of teeth and loss of alveolar bone compared to the control group. The RA patients also had a significantly increased level of serum IgG. In the total material, 26% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(16 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…Comparing periodontal status in 65 RA patients (according to the ACR criteria 1987) with an age-and gender-matched control group (age range 20e70 years) without RA, Mercado et al [42] found that individuals with RA are more likely to experience more periodontal disease (OR 2.2) compared to individuals without RA. Individuals in the RA group showed significant more missing teeth compared to the non-RA group, an observation that confirms previous findings [43,44]. Indicators of disease activity for RA most positively correlated with periodontal bone loss were the number of swollen joints, health assessment questionnaire scores, levels of C-reactive protein and erythrocyte sedimentation rates.…”
Section: The Bradford Hill Approachsupporting
confidence: 89%
“…Comparing periodontal status in 65 RA patients (according to the ACR criteria 1987) with an age-and gender-matched control group (age range 20e70 years) without RA, Mercado et al [42] found that individuals with RA are more likely to experience more periodontal disease (OR 2.2) compared to individuals without RA. Individuals in the RA group showed significant more missing teeth compared to the non-RA group, an observation that confirms previous findings [43,44]. Indicators of disease activity for RA most positively correlated with periodontal bone loss were the number of swollen joints, health assessment questionnaire scores, levels of C-reactive protein and erythrocyte sedimentation rates.…”
Section: The Bradford Hill Approachsupporting
confidence: 89%
“…4165;fax +81 25 228 8771. bacteria associated with periodontal diseases, bone resorption in the foetal rat and destruction of periodontal tissues (Mashimo et al, 1981 ;Vincent et al, 1984). It has been also reported that titres of immunoglobulin (Ig) G and IgA against Eubacterium species are significantly increased in patients with periodontitis (Gunsolley et al, 1990;Martin et al, 1986;Sandholm & Tolo, 1986;Tew et al, 1985;Tolo & Jorkjend, 1990;Tolo & Schenk, 1985). These findings suggest that Eubacterium species may play an important role in the pathogenesis of periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Data from several clinical studies suggested a potential relationship between these disorders and indicated that individuals with rheumatoid arthritis (RA) are more likely to experience periodontal problems compared with healthy counterparts (2,3,(6)(7)(8)(9)(10)(11)(12)(13). The major unanswered question is how autoimmune diseases that tend to affect one or few parts of the body (e.g., joints) could interfere with PD.…”
mentioning
confidence: 99%
“…Both models are plausible but lack convergent data to support them. The majority of existing studies are low-prevalence case-control trials that vary with respect to design, setting, and methods to ascertain the association (6)(7)(8)(9)(10)15). Mechanistic studies are warranted, and the use of experimental models could be suitable in this way.…”
mentioning
confidence: 99%